Analisa Strategi Bisnis Pemasaran Coffee Shop: (Studi pada KAFE KOPI JANJI JIWA Jalan Dr. Wahidin 05 Kota Blitar) - Guntarayana, Indria (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2022)
The research was carried out at the Janji Jiwa Cafe Dr Wahidin 05 street Blitar City with the aim of knowing Strengths, Weaknesses, Opportunities and based on the promotional strategies implemented by the company. In addition, this research was conducted to obtain an alternative strategy used by the Janji Jiwa Cafe Dr Wahidin 05 street Blitar City. The approach that researchers use is a qualitative approach. For data collection the approach used in interviews and documentation. Meanwhile, in describing the results of the research, the SWOT matrix is used through analysis of internal factors and factors from the promotion strategy that is applied by providing an overview of the strengths, weaknesses, opportunities, and threats based on the strategy in promoting the products implemented by the company. The results of the study are based on the SWOT matrix consisting of strengths, weaknesses, opportunities, and threats obtained from the company's promotional strategy. The SWOT matrix is used to generate alternative strategic alternatives which are presented with SO strategy, ST strategy, WO strategy, and WT strategy. From the results of the SWOT analysis, the formulation of the right promotion strategy so that the number of company sales can be increased is the SO (Strengths-Opportunities) strategy through Public Relations (public relations).